Coasters, etc. - Margolies, Maureen L. (Thomson South-Western, 2006)
COASTERS, ETC. is a beginning-level integrated application simulation. This simulation integrates administrative, written communication, and technological skills required to take the user into the 21st century. Working in the marketing department at the amusement park Coasters Etc., students work with Internet, e-mail, electronic scheduling, presentation graphics, and other computerized activities utilizing word processing, spreadsheet, database, and desktop publishing software.